Improving the skills of prospective elementary teachers in designing earth and space science digital teaching materials: TPACK framework - Diki Rukmana; Sri Lestari Handayani (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
This study aims to implement an Earth and Space Science lecture program based on the TPACK framework to improve the skills in designing earth and space learning materials prepared for teaching at the elementary school level by integrating pedagogy and technology. The lecture program is structured based on 3 levels of the TPACK framework where at the first level 3 basic competencies are introduced, namely pedagogical knowledge (PK), content knowledge (CK), and technological knowledge (TK). At the next stage, lecture activities are designed by integrating two of the three basic knowledge, namely pedagogical content knowledge (PCK), technology pedagogical knowledge (TPK), and technology content knowledge (TCK). In the last stage, lecture activities were designed to combine the three basic knowledge aspects, namely technology pedagogical content knowledge (TPCK) into a learning video product. The results show an increase in the TPACK competence of prospective teachers in the medium category. In addition, based on an assessment of the resulting digital teaching products, the TPACK framework-based lecture program is able to facilitate the formation of the skills of prospective teachers in making teaching materials in terms of the appearance of the presentation of teaching materials, content management, and the integration of pedagogical strategies and technology in a good category.